1999
DOI: 10.1007/s000180050486
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of mitochondrial cell death control

Abstract: Mitochondria have been recently recognized to play a major role in the control of apoptosis or programmed cell death. Permeabilization of mitochondrial membranes, a decisive feature of early cell death, is regulated by members of the Bcl-2 family which interact with the permeability transition pore complex (PTPC). Thus, the cytoprotective oncoprotein Bcl-2 stabilizes the mitochondrial membrane barrier function, whereas the tumor suppressor protein Bax permeabilizes mitochondrial membranes. The regulation of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 41 publications
2
27
0
1
Order By: Relevance
“…This observation is in line with the idea (see below) that mitochondria are key players in apoptosis triggered by some, but not all, stimuli (Green and Reed, 1998;Bernardi, 1999;Vieira and Kroemer, 1999;Duchen, 2000). Indeed, according to some authors, the apoptotic process is preceded by collapse of the mitochondrial potential, opening of a multiprotein structure named permeability transition pore (PTP), swelling of the matrix and rupture of the outer membrane with ensuing changes in the permeability of the outer mitochondrial membrane, and release of apoptogenic factors from mitochondria (Petronilli et al, 1994;Skulachev, 1996;Bernardi et al, 1998;Petit et al, 1998); see below.…”
Section: The Ca 2 þ Balletsupporting
confidence: 90%
“…This observation is in line with the idea (see below) that mitochondria are key players in apoptosis triggered by some, but not all, stimuli (Green and Reed, 1998;Bernardi, 1999;Vieira and Kroemer, 1999;Duchen, 2000). Indeed, according to some authors, the apoptotic process is preceded by collapse of the mitochondrial potential, opening of a multiprotein structure named permeability transition pore (PTP), swelling of the matrix and rupture of the outer membrane with ensuing changes in the permeability of the outer mitochondrial membrane, and release of apoptogenic factors from mitochondria (Petronilli et al, 1994;Skulachev, 1996;Bernardi et al, 1998;Petit et al, 1998); see below.…”
Section: The Ca 2 þ Balletsupporting
confidence: 90%
“…This type of permeabilization causes a partial release of proapoptotic factors such as cytochrome c (12,13). The members of the Bcl-2 family also interact with the mitochondrial permeability transition pore (34). Reversible permeabilization of the mitochondrial membrane by opening of the permeability transition pore also causes the release of proapoptotic factors from mitochondria.…”
Section: Breakdown Of Brain Mitochondria By Ca 2ϩ Rise and Hypoxiamentioning
confidence: 99%
“…It is known that mitochondria play a crucial role in several processes and physiopathological situations, including apoptosis. 28,29 First of all, we found that HCW-2 cells did not have MRPs activity higher than HL-60 cells. Furthermore, HCW-2 cells showed resistance also to physical agents like g-rays, thus MRPs must be excluded as a possible mechanism of resistance to apoptosis in such cells.…”
Section: Discussionmentioning
confidence: 65%